KEWENANGAN PENGADILAN TATA USAHA NEGARA (PTUN) DALAM MEMERIKSA DAN MENGADILI SUATU KEPUTUSAN KOMISI PEMILIHAN UMUM (KPU) - Ritonga, Francois Geny; Marbun, Caroline Zilena (Honeste Vivere, 2025)
Disputes can occur in social life and allow for this preservation to occur between the community and State Administrative bodies and/or officials. In particular, this writing allows for the creation of state administration between the community, in this case the members of the district/city level general election commission and State Administration bodies and/or officials, in this case the General Election Commission. The existence of the State Administrative Court has the authority to examine, decide and finalize settlements within the scope of state administration. The authority of the State Administrative Court has been mandated by the provisions of Article 47 of Law Number 5 of 1986 of the State Administrative Court to complete the settlement of state administration as intended in the provisions of Article 1 number 10 of Law Number 51 of 2009 concerning the Second Amendment to Law Number 5 of 1986 concerning Administrative Justice